1991
DOI: 10.1093/clinchem/37.12.2120
|View full text |Cite
|
Sign up to set email alerts
|

Considerations When Measuring Urinary Albumin: Precision, Substances That May Interfere, and Conditions for Sample Storage

Abstract: The measurement of small but abnormal amounts of albumin in urine is important in evaluating kidney disease in people with diabetes mellitus, hypertension, or possible adverse health effects from exposure to nephrotoxins. Routine laboratory methods for measuring albumin are not sensitive enough to measure the amounts that are significant in urine (< 30 mg/L). In our laboratory we used three immunoassays for measuring urinary albumin: enzyme-linked immunosorbent assay (EIA), radioimmunoassay (RIA), and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 6 publications
1
16
0
1
Order By: Relevance
“…Thereafter, samples were divided into aliquots and kept frozen at −20°C until analysis. According to previous studies 23) and our own observations, urine storage at −20°C leads to marginal protein degradation, which is comparable to that seen at −70°C.…”
Section: Blood and Urine Sample Collectionsupporting
confidence: 88%
“…Thereafter, samples were divided into aliquots and kept frozen at −20°C until analysis. According to previous studies 23) and our own observations, urine storage at −20°C leads to marginal protein degradation, which is comparable to that seen at −70°C.…”
Section: Blood and Urine Sample Collectionsupporting
confidence: 88%
“…However, recent studies show that albumin is preserved for least 7 days if stored at 4°C[19–29]. Furthermore, specimen storage at −70°C for 3 months in comparison with specimens analysed fresh did not affect urine proteins[18]. These data suggest that in large longitudinal studies, where the measurement of proteins in fresh urine specimens is often not feasible, it would be preferable to store specimens at −70°C.…”
Section: Discussionmentioning
confidence: 99%
“…Yet several studies have reported a significant underestimation of urine proteins after freezing at −20°C[16–17]. As a result, some authors recommend the use of fresh specimens (4°C for very short periods) or storage at −70°C[18–19] and these methods have been used in several recent studies[14–20]. Immediate analysis of fresh specimens (4°C) is impractical in large longitudinal studies and in the Oxford Regional Prospective Study (ORPS) of childhood diabetes it was opted to change from storage at −20°C to storage at −70°C[21] following these reports.…”
Section: Introductionmentioning
confidence: 99%
“…27 Storage of human urine at −20 C for as little as 2 weeks has been reported to produce modifications to the albumin molecule that may cause mild preanalytic decreases in measured urine albumin concentration. 28,29 Several other studies confirm a timedependent decrease in measured urine albumin concentration at −20 C. [30][31][32] Although some studies suggest that urine can be stored at −70 C or −80 C for much longer periods of time with clinically insignificant changes in urine albumin concentration, these studies do still consistently identify a small, time-dependent decrease in measured concentrations. [32][33][34] Measurement of urine albumin after storage also may be affected by urine pH and method of analysis.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Several other studies confirm a timedependent decrease in measured urine albumin concentration at −20 C. [30][31][32] Although some studies suggest that urine can be stored at −70 C or −80 C for much longer periods of time with clinically insignificant changes in urine albumin concentration, these studies do still consistently identify a small, time-dependent decrease in measured concentrations. [32][33][34] Measurement of urine albumin after storage also may be affected by urine pH and method of analysis. 34,35 Urine creatinine concentrations in urine samples of humans appear to be stable at temperatures ≤-20 C for extended storage times of up to several years.…”
Section: Introductionmentioning
confidence: 99%